Time series of occupational injuries in Saudi Arabia for (896627) registered workers in social insurance during the period according to jobs for the period from 1425 to 1435 H - Badawi, Talal bin Ibrahim (Journal of agricultural, environmental and veterinary sciences, 2017)
This research deals with the statistical analysis of occupational injuries in Saudi Arabia by professions during the period from 1425 to 1435 H using the data available from the Social Insurance (GOSI), which represents the past and the present to extrapolate future values where it is important to plan for the future and watercourses to predict the occurrence of events decisions before they happen at all aspects of the activity, and the research was conducted using a two-component of time series  Seasonal and Cyclical Variationson samples categories of workers by professions All occupations registered the General organization for social Insurance, managers, and the results showed the two high incidence of occupational injuries during the months of Muharram to Shaaban almost with different values in some months, interspersed with the highest increase for the category of total occupations in the Rabe Althani (4), while the least was an increase in the month of Muharram (1) for the category of managers was the highest increase of injuries in the month of Shaaban (8), and the results showed that fewer months a decrease in the incidence of occupational injuries for the two categories are of the month Ramadan, the month of Dhu al-Hijjah, and greater value to decrease the number of injuries for the two categories are in the month of Dhul Hijja (12), and when applying the seasonal guide to predict future injuries for the year 1440 for the two categories they gave values similar to the current results with respect to the increase or decrease in the number of injuries.
Keywords: Time series; occupational injuries; insurances; social